Generational variations in the timing of entry into homeownership in Shanghai: The role of family formation and family of origin. (October 2022) - Mu, Xueying; Cui, Can; Xu, Wei; Cui, Junru
Radical housing reform has triggered tremendous changes in both housing supply and housing demand in China over the past four decades, leading to apparent generational fractures in homeownership. In contrast to the rising age of first dwelling purchasers in some Western countries, younger cohorts in China are entering homeownership at increasingly younger ages despite rising housing prices. Based on a retrospective survey conducted in Shanghai in 2018 and 2019, this study examines the changing roles of family formation and parental background in affecting the timing of entering homeownership across different cohorts. Employing event history analyses, this study demonstrates that transitions to first homeownership have become synchronised with family formation among younger cohorts, which implies the social norm of 'marital home'. Furthermore, the results reveal that parental background is increasingly influential in determining the timing of first home purchase; men and individuals from one-child families are more likely to be the beneficiary of parental help to enter homeownership. Through the lens of cohort, this study contributes to understanding the changing role of family formation and family of origin, which are shaped by institutional and cultural transformations in China. The intensified intergenerational transmission leads to exacerbation of horizontal housing inequality, that is, some achieving homeownership at a younger age while others being shunned from homeownership in the context of worsening housing affordability.